Agricultural Management Options for Climate Variability and Change: Sod-Based Rotation - David Wright; Jim Marois; Clyde Fraisse; Daniel Dourte (EDIS)
A sod-based rotation is when a producer adapts a conventional peanut/cotton rotation by growing a perennial grass, such as bahiagrass, during two years of the rotation. The perennial grass can be grazed, cut for hay or harvested for seed for additional income. Using a sod-based rotation can improve soil water-holding capacity and potentially reduce impacts of dry spells and droughts. This 4-page fact sheet was written by David Wright, Jim Marois, Clyde Fraisse, and Daniel Dourte, and published by the UF Department of Agricultural and Biological Engineering, August 2012.